2015
DOI: 10.11591/.v4i3.4735
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose, but Not Testosterone, Increases Platelet Aggregation Mediated by Endothelial Cells

Abstract: Endothelial cells inhibit platelet aggregation by releasing thromboregulators, such as prostacyclin and nitric oxide. Male subject is a traditional risk factor for cardiovascular diseases. Platelet hyperreactivity has been frequently found in patient with diabetes mellitus. To examine whether testosterone and high glucose modify platelet aggregation through endothelial cells, we did an in vitro study using endothelial cells culture from human umbilical vein (HUVEC). Treatments were performed in HUVEC sub cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Primary HUVEC was successfully performed using enzymatic disaggregation method. The morphological cobblestone of the confluence cells and the expression of von Willebrand factor on endothelial cell membrane have been reported in the researcher's previous reports [13][14].…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Primary HUVEC was successfully performed using enzymatic disaggregation method. The morphological cobblestone of the confluence cells and the expression of von Willebrand factor on endothelial cell membrane have been reported in the researcher's previous reports [13][14].…”
Section: Resultsmentioning
confidence: 66%
“…Any changes in terms of mechanic (pressure) or chemical (including glucose level) in the blood will exert influence to EC. For example, it was reported that high glucose medium depresses the capacity of EC to prevent platelet aggregation [13]. Regarding the influence of high glucose environment to the expression of endothelial COX-2, it still opens to be discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation